Shopping at farmers' markets: Does ease of access really matter?. Issue 5 (5th October 2015) - Shi, Ruoding; Hodges, Alan W.
Abstract: With the rapid growth of farmers' markets, roadside stands and U-pick operations in the USA, direct food distribution to consumers has become more important for agricultural producers. However, numerous studies have revealed that there are barriers preventing further development of these markets. One of the most often cited barriers is lack of access for consumers. This raises the question: to what extent does accessibility affect consumers' participation in this food marketing channel? Based on data from a public mail survey, a binary probit model was developed to test whether the ease of access to farmers' markets would affect consumers' participation decisions. The model included other control variables such as spatial accessibility to other traditional food retail stores, consumer demographics and perceptions of locally produced foods. The results showed that each additional farmers' market within a 5 km radius of the household significantly increased the expected probability of participation by 3.67%, and the effect varied with urban and rural areas. The presence of grocery stores, convenience stores and specialty food stores were statistically insignificant. Also, some demographic characteristics such as age, household income and household size, along with attitudes toward local foods, were found to be significant predictors of consumers' behavior. Finally, we provide a number of implications for improving market locations, targeting interested consumers and developing strategies to promote farmers' markets.